New Thiophene Monolayer-Protected Copper Nanoparticles: Synthesis and Chemical-Physical Characterization. (9th November 2008) - Foresti, Elisabetta; Fracasso, Guido; Lanzi, Massimiliano; Lesci, Isidoro Giorgio; Paganin, Luisa; Zuccheri, Tommaso; Roveri, Norberto
Abstract : For the first time copper 3-(6-mercaptohexyl)thiophene-protected nanoparticles (Cu T6SH) have been synthesized by a one-phase system, utilizing anNaBH 4 /LiCl mixture in diglyme as the reducing reagent and avoiding water medium dissolving copper salts. The prepared nanoclusters, characterized by transmission electron microscopy (TEM), have shown a constant spherical morphology with a size dimension of 5-6 nm in diameter. After their synthesis, no morphological evolution and irreversible aggregation process has been observed after a storage inCH 2 Cl 2 at low temperature for a period up to six months long. Cu T6SH nanoparticles have been investigated by UV-Visible (UV-Vis) and Fourier transmission infrared (FTIR) spectroscopes to characterize the alkylthiophenes monolayer conformations and the particles optoelectronic properties. The UV-Vis reveals the lack of the surface plasmonic band, previously observed in Cu-nanosized clusters at about 556–570 nm, and shows a wide-band centered at 293 nm, probably due to the high-conformational surface ordering of thiophene rings on the Cu core. The results highlight the importance of the modifications ported to the well-known one-phase synthetic reactions to obtain a clear lack, even after a storage of six months, of any irreversible aggregation that has always characterized chain thiophene-protected metallic nanoparticles.